Online Experimentation @FEUP: five years of evaluations - Urbano, Diana; Chouzal, Maria de Fátima; Restivo, Maria Teresa (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR), 2020)
The Online Experimentation @FEUP lab gathers a set of experimental resources based on Augmented Reality, Virtual Reality and Haptic Systems. The design, development and implementation of those resources are guided by the following main goals: familiarizing students with the referred technologies, complement hands-on experimentation, motivate students and promote knowledge gain. A brief presentation of the online experimental activities most utilized and evaluated in the past five years in context of different undergraduate courses and at the K12 level is presented. In all the studies conducted, the strategies adopted involve pre- and post-testing to assess knowledge gain, experimental group activities, and individual response to surveys to assess student reaction. The results published in journals, conferences proceedings and book chapters are discussed.